2010
DOI: 10.1097/dad.0b013e3181c70d88
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Involvement: What Does it Mean?

Abstract: Perineural invasion is an important mechanism for local spread in certain malignant cutaneous neoplasms and is associated with aggressive tumor growth, increased frequency of recurrence, and increased morbidity and mortality. Thus, perineural invasion is often used both as a marker of malignancy and an indicator of aggressive behavior. There exists, however, a limited number of cutaneous and noncutaneous benign neoplasms in addition to reactive lesions that either demonstrates perineural involvement or mimics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…The reported incidence of PNI in H&E evaluated cSCCs varies substantially, with a range of 2% to 14%, although most studies report rates between 2% and 5% [6,11,18]. However, comparisons of PNI incidence are complicated by multiple factors that include the challenges associated with detection of PNI using H&E staining (obscured nerve and morphologically imperceptible tumor cells); lack of a standardized histologic definition of PNI (delineating true PNI from focal abutment secondary to impingement of nerve by tumor); differences in detection rates between cryostat and formalin-fixed, paraffinembedded tissue sections (Mohs micrographic surgery versus traditional histopathologic examination); and histologic mimics such as Renault bodies, perineural fibrosis, reactive neuroepithelial aggregates, and reparative perineural hyperplasia [3,18,20,21,[31][32][33]. Findings from our study, which, to the best of our knowledge, is the first to specifically compare PNI in SCCs from the H&N versus non-H&N areas, indicate that there may be an increased incidence of PNI in the former.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of PNI in H&E evaluated cSCCs varies substantially, with a range of 2% to 14%, although most studies report rates between 2% and 5% [6,11,18]. However, comparisons of PNI incidence are complicated by multiple factors that include the challenges associated with detection of PNI using H&E staining (obscured nerve and morphologically imperceptible tumor cells); lack of a standardized histologic definition of PNI (delineating true PNI from focal abutment secondary to impingement of nerve by tumor); differences in detection rates between cryostat and formalin-fixed, paraffinembedded tissue sections (Mohs micrographic surgery versus traditional histopathologic examination); and histologic mimics such as Renault bodies, perineural fibrosis, reactive neuroepithelial aggregates, and reparative perineural hyperplasia [3,18,20,21,[31][32][33]. Findings from our study, which, to the best of our knowledge, is the first to specifically compare PNI in SCCs from the H&N versus non-H&N areas, indicate that there may be an increased incidence of PNI in the former.…”
Section: Discussionmentioning
confidence: 99%
“…Re‐excision perineural invasion is characterized histopathologically by the presence of mature epithelium within the perineural space at the site of previous surgical procedure . Displacement of eccrine epithelial cells into the perineural space by mechanical force(s) during surgery has been suggested as the most likely pathogenetic mechanism . Although epithelial cells in the perineural space generally display bland morphological features, the presence of focal atypia of epithelial cells has also been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Reactive epithelial proliferations within the peripheral nerves occurring in the skin mimicking perineural invasion generally include epithelial sheath neuroma, re‐excision perineural invasion and reactive neuroepithelial aggregates . The main importance of these proliferations lies in their distinction from true perineural invasion developing in the background of malignant tumors of different lineage, a phenomenon usually associated with more aggressive clinical behavior, including increased risk for local recurrence with a potential for increased morbidity and mortality …”
mentioning
confidence: 99%
“…Furthermore, it has been suggested that rates of PNI are higher in cSCCs of the head and neck (H&N) compared to other anatomic sites which may confound past reports (Chang et al, 2004). Comparisons of PNI incidence are complicated by multiple factors that include the challenges associated with detection of PNI using hematoxylin and eosin (H&E) staining (obscured nerve and morphologically imperceptible tumor cells), lack of a standardized histological definition of PNI (delineating true PNI from focal abutment secondary to impingement of nerve by tumor), differences in detection rates between cryostat and formalinfixed paraffin-embedded tissue sections (Mohs micrographic surgery vs traditional histopathologic examination), and histological mimics such as Renault bodies, perineural fibrosis, reactive neuroepithelial aggregates, and reparative perineural hyperplasia (Campoli et al, 2014;Dunn, Morgan, Beer, Chen, & Acker, 2009;Hassanein et al, 2005;Kurtz, Hoffman, Zimmerman, & Robinson, 2005;Ronaghy, Yaar, Goldberg, Mahalingam, & Bhawan, 2010;Zhou, Xu, Zhang, Zhao, & Wu, 2014). Lastly, in select cutaneous and noncutaneous malignancies it has been shown that the use of immunohistochemistry (IHC) can aid in the detection of PNI, especially in the tumor bulk where nerve can be obscured by tumor (intratumoral PNI) (Berlingeri-Ramos, Detweiler, Wagner, & Kelly, 2015;Kurtz et al, 2005;Scanlon et al, 2014;Zhou et al, 2014).…”
Section: Incidence Of Pni In Cutaneous Malignanciesmentioning
confidence: 98%